柴油机曲轴滑动轴承异常振动试验与研究 - 蒙留纪; 蒙倩娜 (Jixie chuandong)
By the experimental apparatus,test,data collection,analysis and comparison are carried out,and the vibration signals of steady-state and non-steady state are measured when the sliding bearing of diesel engine in abnormal gap. By the vibration characteristics of bearings and shaft after worn,the frequency characteristics,peak value and speed of the test results and otherwise are studied. The accurate diagnosis and prediction for increasing gap and vibration after bearings worn are ashieved.